Deterministic Estimation of Stripe Type Defects and Reconstruction of Mask Pattern in L/S Type Mask Inspection - Kim, Wooshik; Park, Min-Chul (OPTICAL SOC KOREA, 2015)
In this paper, we consider a method for estimating a stripe-type defect and the reconstruction of a defect-free L/S type mask used in lithography. Comparing diffraction patterns of defected and defect-free masks, we derive equations for the estimation of the location and size of the defect. We construct an analytical model for this problem and derive closed form equations to determine the location and size using phase retrieval problem solving techniques. Consequently, we develop an algorithm that determines a defect-free mask pattern. An example shows the validity of the equations.
Keywords: PHASE RETRIEVAL; ALGORITHMS